Synthesis, Characterization, and Biological Activity Studies of Copper(II) Mixed Compound with Histamine and Nalidixic Acid - Bivián Castro, Egla Yareth; López, Mercedes G.; Pedraza Reyes, Mario; Bernès, Sylvain; Mendoza Díaz, Guillermo (2009)
A mixed copper complex with deprotonated nalidixic acid (nal) and histamine (hsm) was synthesized and characterized by FTIR, UV-Vis, elemental analysis, and conductivity. The crystal structure of [Cu(hsm)(nal)H2O]Cl·3H2O (chn) showed a pentacoordinated cooper(II) in a square pyramidal geometry surrounded by two N atoms from hsm, two O atoms from the quinolone, and one apical water oxygen. Alteration of bacterial DNA structure and/or associated functions in vivo by [Cu(hsm)(nal)H2O]Cl·3H2O was demonstrated by the induction of a recA-lacZ fusion integrated at the amyE locus of a recombinant Bacillus subtilis strain. Results from circular dichroism and denaturation of calf thymus DNA (CT-DNA) suggested that increased amounts of copper complex were able to stabilize the double helix of DNA in vitro mainly by formation of hydrogen bonds between chn and the sugars of DNA minor groove. In vivo and in vitro biological activities of the chn complex were compared with the chemical nuclease [Cu(phen)(nal)H2O]NO3·3H2O (cpn) where phen is phenanthroline.